2019
DOI: 10.1002/jcp.28941
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes from human‐bone‐marrow‐derived mesenchymal stem cells protect against renal ischemia/reperfusion injury via transferring miR‐199a‐3p

Abstract: Renal ischemia/reperfusion (I/R) injury is the main reason for acute kidney injury (AKI) and is closely related to high morbidity and mortality. In this study, we found that exosomes from human-bone-marrow-derived mesenchymal stem cells (hBMSC-Exos) play a protective role in hypoxia/reoxygenation (H/R) injury.hBMSC-Exos were enriched in miR-199a-3p, and hBMSC-Exo treatment increased the expression level of miR-199a-3p in renal cells. We further explored the function of miR-199a-3p on H/R injury. miR-199a-3p wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
104
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(104 citation statements)
references
References 50 publications
0
104
0
Order By: Relevance
“…Liu and Zheng [34] found that BMSC transplantation attenuates inflammation, oxidative stress, and fibrosis in skeletal muscle after muscle contusion. In addition, BMSC infusion has been reported to improve recovery from the acute kidney injury (AKI) induced by ischemia/reperfusion [10]. However, BMSCs can also be tumorigenic and are often inappropriately retained by target tissues, limiting their clinical usefulness [9].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Liu and Zheng [34] found that BMSC transplantation attenuates inflammation, oxidative stress, and fibrosis in skeletal muscle after muscle contusion. In addition, BMSC infusion has been reported to improve recovery from the acute kidney injury (AKI) induced by ischemia/reperfusion [10]. However, BMSCs can also be tumorigenic and are often inappropriately retained by target tissues, limiting their clinical usefulness [9].…”
Section: Discussionmentioning
confidence: 99%
“…EVs, which are typically approximately 40-200 nm in size [10], can be categorized as exosomes, microvesicles and apoptotic bodies. EVs are membranous bodies that are released by almost all cells [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(Dominguez et al, 2018) Therapeutics MSCs (human) Exosomes derived from bone marrow MSCs were rich with miR-199a-3p and could prevent ischemia/reperfusion-induced AKI by increasing expression of miR-199a-3p in renal cells. (Zhu et al, 2019a) Sepsisinduced AKI Biomarker Urine (human) Increased urinary exosomal NGAL and activating transcription factor 3 in sepsis-induced AKI patients. (Panich et al, 2017) Biomarker…”
Section: Exosome and The Renal Physiologymentioning
confidence: 99%